The prisoner of Zenda - Hope, Anthony, 1863-1933. (London : Longmans, Green and Co.Ltd., 1946)
He has the appearance and manner of the king, yet he$1 (Bs really a lookalike ... and on his shoulders rests all hope of foiling a blackguard$1 (Bs plot to usurp the throne. Adventure, pageantry and royal intrigue are forged at sword point. s
Keywords: Kings and rulers -- Succession -- Drama